2014
DOI: 10.1155/2014/985306
|View full text |Cite
|
Sign up to set email alerts
|

Elizabethkingia meningosepticumin a Patient with Six-Year Bilateral Perma-Catheters

Abstract: Elizabethkingia meningosepticum (EM) is a saprophyte which is ubiquitous in nature, but not normally present in the human flora. Instances of infection are rare in the USA, but EM may be an emerging pathogen among immune-compromised patients. EM can cause a variety of infections, but nosocomial pneumonia and bacteremia have been the most commonly reported among immune-compromised adults. EM has proven difficult to treat with a mortality rate of 23%–41% in adult bacteremia. This is likely due to its resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Our patient had a longstanding history of diabetic nephropathy which necessitated chronic hemodialysis therapy. Importantly, E. meningoseptica bacteremia has been described in patients with a wide array of renal pathology which required chronic hemodialysis therapy [9] , [10] , [11] , [12] , [13] , [14] . Our patient potentially developed catheter-related bacteremia considering its ability to contaminate medical devices and the blood cultures positive for E. meningoseptica through the hemodialysis catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had a longstanding history of diabetic nephropathy which necessitated chronic hemodialysis therapy. Importantly, E. meningoseptica bacteremia has been described in patients with a wide array of renal pathology which required chronic hemodialysis therapy [9] , [10] , [11] , [12] , [13] , [14] . Our patient potentially developed catheter-related bacteremia considering its ability to contaminate medical devices and the blood cultures positive for E. meningoseptica through the hemodialysis catheter.…”
Section: Discussionmentioning
confidence: 99%
“…Echeverri et al reported a case of bacteremia in a patient with history of acute lymphoblastic leukemia, initially treated with moxifloxacin, then combined with vancomycin and sulfamethoxazole [10]. E. meningoseptica bacteremia has also been described in patients requiring chronic hemodialysis therapy [11][12][13][14][15][16]. A study from Taiwan on the analysis of adult patients with E. meningoseptica bacteremia showed that 86% of the patients had nosocomial infections and 60% had acquired the infection in the ICUs [17].…”
Section: Discussionmentioning
confidence: 99%
“…CT brain showed pneumocephalus. Total leucocyte count (TLC) was 13,200 cells/mm 3 (4500-11000), hemoglobin 15.5 g/dL (13)(14)(15), sodium 138 meq/L (145-150), potassium 4.6 meq/L (3.5-5.5) and chlorides were 107 meq/L (96-106). Patient was drowsy and not obeying commands and hence shifted to intensive care unit (ICU).…”
Section: Case Reportmentioning
confidence: 99%
“…meningosepticum has a characteristic profile for antibiotic susceptibility. The organism is resistant to antimicrobials to which gram-negative bacteria are susceptible such as aminoglycosides, β-lactams and carbapenems but is surprisingly susceptible to drugs prescribed for treatment of grampositive bacteria including vancomycin, rifampicin and trimethoprim-sulfamethoxazole (13). This characteristic pattern of antimicrobial susceptibility may make it difficult to select appropriate drugs.…”
Section: Discussionmentioning
confidence: 99%